PERENCANAAN CO-HOUSING UNTUK GENERASI MILENIAL DENGAN PENERAPAN ARSITEKTUR EKOLOGI DI MANADO, SULAWESI UTARA - Geraldine Gracia Elkanatane; Anggraeni Dyah; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2022)
Co-Housing is generally a residential concept where the residents of the house have formed a community before the housing is built, where they participate in designing housing designs. Communal facilities in Co-Housing can be in the form of a shared room, shared dining room, kitchen, swimming pool, laundry room, play ground, warehouse, workshop to shared sports facilities. The concept of Co-housing planning with the applied ecological architecture is expected to be able to adapt to the financial conditions of the millennial community in Manado, starting from the application of affordable materials, community budget plans, to the application of shared spaces for the millennial community. This study aims to help provide alternative residential housing that provides something new to housing in Indonesia, especially in the city of Manado, North Sulawesi, which facilitates social interaction in a residential environment that currently tends to be individualistic.